2007
DOI: 10.1007/s00405-007-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and radiological investigations of the influence of botulinum toxin on the submandibular gland of the rat

Abstract: The aim of the study was to correlate the sonographic features of Botox A injection in rat submandibular gland with the histopathological changes. Fifteen Wistar albino rats were randomly assigned to 2 groups. Group 1 (control group) consisted of 5 animals not given any substance. Group 2 was divided as "a" and "b" each consisting of 5 animals. A median cervical incision has been performed to the rats in group 2 and 2.5 U Botulinum toxin A reconstituted 0.1 ml physiologic saline was injected into the right gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…Thus, these authors Yuan, Hou and Wen (2004) and Coskun et al (2007), agree in saying that botulinum toxin type A temporarily induces atrophy of acinar cells. However, disagree on the point regarding on whether or not there is leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, these authors Yuan, Hou and Wen (2004) and Coskun et al (2007), agree in saying that botulinum toxin type A temporarily induces atrophy of acinar cells. However, disagree on the point regarding on whether or not there is leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 82%
“…Teymoortash et al (2007), affirm that in the first study performed by Ellies et al (1999), morphometric evaluations were limited to the description of serous acinar cell nuclei and did not use a standard method of fixation to minimize differences in shrinkage of the tissue samples. Coskun et al (2007), in addition to histological processing, used radiological studies before and after application of the toxin in submandibular gland of rats, observed reduction in size of the glands, but with no permanent histological changes in the cells. There was no change in the vascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regeneration of prostate volume at 2 weeks thus seems to disagree with the duration of effect for BTX-A. Coskun et al [15] have also shown that BTX-A injection does not exert any direct effects on cells in the submandibular gland, but causes homogenic reductions in gland size without apoptosis, while Rohrbach et al [16] reported that injection of BTX-A into the nasal gland in guinea pigs induces apoptosis. In addition, clinical research has shown no change in prostate volume on magnetic resonance imaging in a sham double-blind study using 200 U of BTX-A or saline in 30 patients [17] .…”
Section: Discussionmentioning
confidence: 95%
“…Etkinin bu kadar uzun sürmesinin nedeni sempatik sinir liflerinde SNAP-25 proteininin tekrar oluflturulmas›n›n uzun zaman almas› veya aksonal filizlenmenin sempatik sinir liflerinde yavafl seyretmesinden olabilir. Botulinum toksini ter bezlerinde atrofiye yol açmaz (22). Hiperhidrozisin tedavisinde yeni bir BT-A preparat› olan Xeomin ® 'in ve BT-B'nin (Myobloc ® veya Neurobloc ® ) de etkili oldu¤u bildirilmifltir (23,24).…”
Section: Hiperhidrozisunclassified